Journal of Intensive Care - Gando, Satoshi; Morisaki, Hiroshi
Journal of Intensive Care is an open access journal encompassing all aspects of intensive care medicine, such as intensive and critical care, trauma and surgical intensive care, pediatric intensive care, acute and emergency medicine, perioperative medicine, resuscitation, infection control and organ dysfunction. In addition, the journal encourages submissions considering the different cultural aspects of intensive care practice.